Being naked on the internet: young people's selfies as intimate edgework. (16th March 2017) - Hart, Matt
ABSTRACT: In this paper, I examine how young selfie sharers engage in intimate edgework in the visual social media site tumblr. Originally devised by Stephen Lyng, edgework is defined as the purposeful engagement in risky behaviour as a result of the seductive character of the experience, and the rewards of doing so brings. The article is based on data gathered from in-depth, online interviews with 25 young people who post naked self-photographs to their tumblr blogs, and participant observation between mid-2014 and late 2015. Through their online practices, I show how young selfie sharers gain a range of benefits similar to those leveraged by people engaged in archetypal forms of edgework – such as skydivers – without the threat of physical danger. Young people negotiate the societal boundaries of morality/immorality and order/disorder; prepare and deploy specific skills in their edgework; and maintain a perception of control. Through being naked on the internet, young people feel a sense of well-being and belonging, thus engaging in 'intimate edgework'. This article answers the call for further development of a feminist model of edgework that uproots its original hegemonic masculine ideals by elaborating on how individuals negotiate emotional edges in the digital age.